Trouble-maker - Clements, Andrew, 1949-2019 (Atheneum Books for Young Readers, 2013)
When his older brother gets in serious trouble, sixth-grader Clay decides to change his own mischief-making ways, but he cannot seem to shake his reputation as a troublemaker.